If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1-2(e-1)=13-4(3e-5)
We move all terms to the left:
1-2(e-1)-(13-4(3e-5))=0
We multiply parentheses
-2e-(13-4(3e-5))+2+1=0
We calculate terms in parentheses: -(13-4(3e-5)), so:We add all the numbers together, and all the variables
13-4(3e-5)
determiningTheFunctionDomain -4(3e-5)+13
We multiply parentheses
-12e+20+13
We add all the numbers together, and all the variables
-12e+33
Back to the equation:
-(-12e+33)
-2e-(-12e+33)+3=0
We get rid of parentheses
-2e+12e-33+3=0
We add all the numbers together, and all the variables
10e-30=0
We move all terms containing e to the left, all other terms to the right
10e=30
e=30/10
e=3
| z-19=-2 | | 2x+5=3-7x | | -10|x+2|=-70 | | 126=7(8+5x) | | 10x+29=4x-9 | | 6(-7x+7)=126 | | 2x-7/3=3x+1/5 | | 10x29=4x-9 | | 36=w/3+9 | | 14.75x+62=180 | | x+20-1/5(x+20)=4x | | 2-3(3x+7)=-82 | | 6/f=2.5 | | g-3=1.6 | | 1/4+1/5+1/6-14=x/2 | | 7(x+2)–4(x-3)=0 | | 20-3n=2 | | -16x^2+48x+28=48 | | 25x-3=100 | | 14-b=10 | | 4p-3=13(p=-4) | | x/4+x/5+x/6-14=x/2 | | 4-2(x-7)=-6 | | 2(5x+8)=-8x-2(1-6x) | | 4p-3=13(p=4) | | (2t-4)=20-2t | | 6x-9=-5x+24 | | 5(b-6)=8(b+9) | | 116=-8(6x+5)-4x | | y/2+5=-17 | | 4+2p=1-(3/5p-2) | | 60+45f=57.95f |